Jobs, Technology and People / Psychology Focus - Chmiel Nik (Rouledge, 1998)
This book provides an accessible introduction to key issues in occupational psychology. Technology and Work Psychology, Jobs and Tasks, Technology and Personnel, Mental Work, Work Safety in Complex Technological Systems, Team-working and Technology, Concluding Remarks.